Pedagogical content knowledge of pre-service physics teachers - Fariyani, Qisthi; Mubarok, Ferry Khusnul; Masfu’ah, Siti; Syukur, Fatah (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2020)
This study aims to describe the content knowledge, pedagogical knowledge, and pedagogical content knowledge of students of pre-service physics teachers at Walisongo Semarang. The type of research is quantitative descriptive. The samples were Physics Pre-service teachers at Universitas Islam Negeri Walisongo Semarang. The samples were 65 pre-service physics teachers determined by the purposive sampling technique. The method of collecting data used was a test, observation, and documentation. The results showed that pre-service physics teachers' content knowledge capabilities were in three categories, namely: 35% poor, 42% sufficient, and 23% good. The pedagogical knowledge test showed that 16% of physics pre-service teachers were in a good category, 77% were in a good category, and 7% were in a very good category. The results of the pedagogical content knowledge test showed that 12% of the pre-service physics teachers were in the poor, 30% were in the moderate category, 35% were in a good category, and 23% were in the very good category. Pre-service physics teachers had the lowest ability in determining other factors that influence teaching concepts, and the highest ability in determining important science concepts in the material to be taught. This research implies that remediation is needed to improve physics pre-service teachers' Pedagogical Content knowledge capabilities, which can be applied in the Plan of Learning course